Rancang Bangun Alat Pengemas Biji Kopi Otomatis Berbasis Arduino Uno - ., Zaenurrohman; Julian Nurachman Wijaya; Sugeng Dwi Riyanto; Hera Susanti (Politeknik Negeri Cilacap, 2024)
Before coffee products are marketed, packaging is generally carried out first. Apart from protecting against damage, the packaging also aims to make it easier to carry while traveling. The conventional packaging process is quite time and energy consuming. This results in the packaging process being less efficient. With an automatic packaging system, it is hoped that it will make things easier and save time and energy. Automatic coffee bean packaging tools are built using several electronic devices. Arduino Uno is used as a controller, a load cell sensor to weigh the coffee packaging, a DS18B20 temperature sensor to measure the temperature of the packaging sealer and a proximity sensor to detect plastic packaging. In the actuator section, a servo motor is used to open the coffee bean reservoir valve (hopper tank), a DC motor is used to pull the packaging plastic and a stepper motor is used to press the packaging plastic. The plastic press is equipped with a heating mechanism using nickel wire so that the two layers of plastic can stick together. An LCD module is used to display information on the weight value of the coffee packaging, the temperature value of the sealer and the status of the packaging process. From the test results, it is known that the coffee bean packaging tool is capable of packaging coffee beans automatically. Coffee beans can be packaged in plastic with the weight and length of the packaging according to the design with a success rate of up to 87.5%